Studies on influence of hydrogen and carbon monoxide concentration on reduction progression behavior of molybdenum oxide catalyst - Samsuri A.; Latif M.N.; Shamsuddin M.R.; Salleh F.; Abu Tahari M.N.; Tengku Saharuddin T.S.; Dzakaria N.; Yarmo M.A. (Elsevier Ltd, 2024)
Indexed by SCOPUS/ERA